Statistical analysis of the financial state of the banking sector - O. G. Tretyakova; T. I. Chinaeva (Статистика и экономика)
Purpose of the study. The aim of the work is to study the state ofthe banking sector of the country based on the analysis of the main indicators, characterizing banking activity in modern  conditions, studying the main factors, affecting the financial result of banks. An important direction in analyzing the banking sector is to  determine its reliability and sustainability. Reliability, stability of the  country’s banking system is largely determined by the financial  performance of banks. In the paper, the main tendencies of  development of the banking sector are considered, based on  economic and statistical methods the analysis of its financial state is  carried out. The work is based on dynamic, structural, factor analysis of analytical and statistical information about the processes, taking place in this field.Materials and methods. Information base of the research is statistical data and analytical information reflecting the financial  activity of the banking sector. The methodological basis for the study is statistical methods of data analysis: comparative and structural  analysis, dynamics, and correlation-regression analysis.Results. The main indicators of the bank resource base and efficiency of its use are considered. The main trends of changes in  the structure of bank liabilities and assets are analyzed, and the  analysis of the ratios of loans and deposits is given. Financial  analysis of the state of the banking sector involves studying factors  that affect the activities of banking institutions. It is important not  only to determine the factors themselves, but also the degree of  their impact on the results of the bank’s work. For this purpose, the  paper used correlation-regression analysis, on the basis of which the main factors that influenced the financial result of the banking  system in 2016 were studied.Сonclusion. The analsis showed that customers borrow the largest share in the structure of the passive base of the Russian banking sector. For the period, considered in the paper, deposits of  individuals and corporate clients increased. The share of loans and  deposits received from the Bank of Russia declined, while the share  of loans and deposits received from other credit institutions grew at  the same time. Thus, in the structure of liabilities, the funds of the Bank of Russia are replaced by other, market sources. As a positive  trend, we can note the growth of profits and funds of credit  institutions in the liabilities of the banking sector. The main direction  of using banking assets is lending to the economy. In the structure  of assets, the share of loans and other loans was about 70%. In  2016, the volume of loans granted to the economy as a whole,  decreased  by 3%. Overall, for the period under review, the total  revenues of the banking sector decreased by 4.9%. The main factor  in reducing revenues was their significant reduction from operations  with foreign currency. The correlation-regression analysis of the  factors influencing the formation of the profit of the banking sector  showed that the most significant value is the volume of loans.  Quantitative measurement of the influence of this factor is the basis  for further analysis of the financial sector of the economy,  construction of forecast calculations.